The impact of coworker guanxi on workers’ safety behaviors in the construction industry: the effects of team identification, team knowledge sharing, and team safety climate - Wang, Lixia; Luo, Xun; Li, Hujun (Frontiers in Public Health, 2025)
This study explores how coworker guanxi (CG) influences workers’ safety behaviors (WSBs) in China’s construction industry, focusing on the mediating roles of team identification (TI) and team knowledge sharing (TKS), and the moderating effect of team safety climate (TSC). Based on social exchange theory and previous literature, the research proposes a dual-mediation model to capture the complex interplay between these factors. A survey was conducted with 347 frontline construction workers across three major Chinese cities to test the hypotheses. Latent variable models revealed that CG has a significant positive impact on WSB, both directly (β = 0.155, p < 0.001) and indirectly through TI (indirect effect = 0.216) and TKS (indirect effect = 0.230). The results also showed that TSC moderates the relationship between CG and both TI and TKS, amplifying the positive effects on safety behaviors in construction teams. These findings offer important theoretical contributions by integrating CG into safety behavior research and extending social exchange theory in the context of Chinese construction environments. Additionally, the study provides practical insights for construction managers, suggesting that fostering strong coworker relationships and a positive safety climate can significantly improve safety behaviors, ultimately reducing workplace accidents and enhancing overall safety performance.